Conclusion: Energy ethics and ethical worlds. (14th March 2019) - Appel, Hannah
Abstract: What happens when the effects of our ethical actions stretch beyond, often far beyond, first‐ and second‐person phenomena? What happens when one person's richly textured ethical world is another's profound violation? Energy offers a particularly useful empirical terrain on which to think through the questions posed by ethical worlds. Ethical worlds gesture both to the supra‐individual, supra‐present contexts in which we all craft quotidian ethics, and to the expansive geographies and timescapes in which the effects of our ethical practices ramify. Ethical worlds, fields, or landscapes are not bordered by first‐ or second‐person experiences, but rather they intersect and interfere with one another often at great distance, often over multiple generations, and certainly not equally. Ethical practices in more powerful fields spill out, invade, and give shape to ethical practices in other ethical fields. What does it mean to start to see and feel and analyse at these ethical crossroads? In particular, what might it mean to acknowledge that structure, power, and interest – which are too often arrayed against close ethnographic attention to individual and shared experience – are not 'larger forces' but other ethical worlds, equally amenable to ethnographic attention?